Multimodal magnetic resonance imaging of youth sport-related concussion reveals acute changes in the cerebellum, basal ganglia, and corpus callosum that resolve with recovery - Pinky, Najratun Nayem; Debert, Chantel T.; Dukelow, Sean P.; Benson, Brian W.; Harris, Ashley D.; Yeates, Keith O.; Emery, Carolyn A.; Goodyear, Bradley G. (Frontiers in Human Neuroscience, 2022)
Magnetic resonance imaging (MRI) can provide a number of measurements relevant to sport-related concussion (SRC) symptoms; however, most studies to date have used a single MRI modality and whole-brain exploratory analyses in attempts to localize concussion injury. This has resulted in highly variable findings across studies due to wide ranging symptomology, severity and nature of injury within studies. A multimodal MRI, symptom-guided region-of-interest (ROI) approach is likely to yield more consistent results. The functions of the cerebellum and basal ganglia transcend many common concussion symptoms, and thus these regions, plus the white matter tracts that connect or project from them, constitute plausible ROIs for MRI analysis. We performed diffusion tensor imaging (DTI), resting-state functional MRI, quantitative susceptibility mapping (QSM), and cerebral blood flow (CBF) imaging using arterial spin labeling (ASL), in youth aged 12-18 years following SRC, with a focus on the cerebellum, basal ganglia and white matter tracts. Compared to controls similar in age, sex and sport (N=20), recent SRC youth (N=29; MRI at 8 ± 3 days post injury) exhibited increased susceptibility in the cerebellum (p = 0.032), decreased functional connectivity between the caudate and each of the pallidum (p=0.035) and thalamus (p=0.021), and decreased diffusivity in the mid-posterior corpus callosum (p < 0.038); no changes were observed in recovered asymptomatic youth (N=16; 41 ± 16 days post injury). For recent symptomatic-only SRC youth (N=24), symptom severity was associated with increased susceptibility in the superior cerebellar peduncles (p=0.011) and reduced activity in the cerebellum (p=0.013). Fewer days between injury and MRI were associated with reduced cerebellar-parietal functional connectivity (p<0.014), reduced activity of the pallidum (p=0.002), increased CBF in the caudate (p=0.005), and reduced diffusivity in the central corpus callosum (p<0.05). Youth SRC is associated with acute cerebellar inflammation accompanied by reduced cerebellar activity and cerebellar-parietal connectivity, as well as structural changes of the middle regions of the corpus callosum accompanied by functional changes of the caudate, all of which resolve with recovery. Early MRI post-injury is important to establish objective MRI-based indicators for concussion diagnosis, recovery assessment and prediction of outcome.